Design and Development of a 3-DOF Personal Motion Simulator - Yong-Ho Seo (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study describes the design and development of a motion simulator with 3 degrees of freedom as a personal riding motion simulator. While the conventional motion simulator mainly pursues high precision with high performance specifications, we propose a simple and cost effective riding motion simulator to replace the expensive conventional motion simulator. In this paper, we propose a new motion platform with a parallel mechanism that can be implemented stably because the mechanism structure has higher inertia moment and force transmission efficiency than the serial type mechanism. The proposed motion simulator needs to be configured to have minimal degree of freedoms while a user experiences a proper motion. Therefore, we design a three-degree-of-freedom parallel mechanism that can be implemented stably due to high inertia moment and force transmission efficiency, and verify the performance of the simulator through experiments.